Target Selection in Multistatic Microwave Breast Imaging Setup Using Dielectric Lens - Godinho, Daniela M. (2022)
Microwave Imaging (MWI) has been studied to aid early breast cancer detection. Current prototypes in more advanced stages of development include both monostatic or multistatic setups. However, multistatic configurations usually include a high number of antennas which consequently require complex and computationally-intensive signal processing algorithms to ensure a good target detection. We previously presented a novel approach using a dielectric lens which reduces the signal processing burden of multistatic setups, while ensuring good spatial resolution. In this paper, we evaluate this novel setup using an anatomically realistic breast phantom and its capability of selecting targets inside the breast. We show a successful detection of the targets using an artefact removal algorithm based on singular value decomposition when the Bessel beam is centered at the target location.